Effectiveness of Satintelkam Early Detection for Disorder Identification of Kamtibmas on the Construction of the Kertosono-Kediri Toll Road in the Nganjuk Region (Advances in Police Science Research Journal, 2024)
The author raised this final assignment with the problem "Effectiveness of Satintelkam Early Detection to Identify Public Security Disturbances in the Construction of the Kertosono - Kediri Toll Road, Nganjuk Legal Area. The research purpouse was knew the implementation of the early detection system implemented by the Nganjuk Police Satintelkam and find out what factors make the implementation of the early detection system run optimally. A qualitative approach was used in this research and used descriptive analytical research. Interviews with sources, observations and also document studies were carried out by the author to be able to fulfill and complete the required data.To fulfill the research objectives, the author uses management theory put forward by Henry Fayol and also performance theory. The author also uses several concepts to complete the discussion in the research, namely the concept of early detection and the concept of security and social order based on article 1 of the National Police Law Number 2 of 2002 concerning Security and Order. The Early Detection Activities of the Nganjuk Police SatIntelkam have an important role in preventing social security. Several finding in the planning and supervision that were not in accordance with Perkap No. 1 of 2019 concerning the Police Operational Management System. The author also impeding factors hampered the implementation of early detection by Unit II of the Nganjuk Police SatIntelkam internally. Therefore, the author saw the need essential breakthrough provision to improve the performance of the Nganjuk Police Intelligence and Security unit in order.
Keywords: Kata kunci : Deteksi Dini, Intelkam, Pembangunan jalan tol, Kertosono – Kediri